(untitled) (Comprehensive Journal of Science, 2025)
This study aims to explore the implications of economic crises in Libya and the resulting shifts in consumer behavior patterns, particularly concerning purchasing decisions for different product categories (essential goods, non-essential goods, luxury items, and electronics). To achieve this objective, a descriptive-analytical research methodology was adopted as the most suitable approach for accurately understanding and describing the phenomenon under investigation. Data were collected through a survey of a sample of Libyan consumers using a questionnaire specifically designed for this purpose. The collected data were then analyzed using appropriate statistical tests via the Statistical Package for the Social Sciences (SPSS, version 22). The study yielded several key findings, the most significant of which include: the current economic crisis has profoundly impacted consumers’ personal income; rising inflation rates have made it increasingly difficult to secure essential goods. Additionally, the depreciation of the Libyan dinar has significantly reduced purchasing power, while cash liquidity shortages have constrained consumer spending, forcing individuals to adopt strict expenditure rationing strategies to cope with the prevailing difficult economic conditions.The study recommends addressing the cash liquidity crisis by developing more efficient cash distribution mechanisms and promoting the use of secure electronic payment methods to reduce overreliance on physical cash and facilitate daily transactions for citizens. Furthermore, it emphasizes the importance of enhancing individual financial planning and promoting responsible consumption among consumers, especially during economic crises, through community-based financial literacy programs and encouraging the use of personal budgeting tools.